SOME GEOMETRIC CURVES IN THE SENSE OF D-SEGMENT - Галущак, Світлана Ігорівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We have constructed some geometric curves in the sense of d -segment in metric spaces(R^2,d_1) and (R^2 , d_∞). The notion of d -convexity as well as examples of d -convex and weakly convex sets are also considered.